Desenvolvimento e aplicação de uma metodologia para avaliação da capacidade dos mordentes de mandris de bobinadeiras de laminadores a frio tipo sendzimir - Antonio Carlos Ataide (2011)
In this work the development of a methodology is presented for evaluation of the capacity of the mandrel grippers of the coilers of Sendzimir cold rolling mills. The grippers are mechanisms composed of bars with hydraulic performance, whose function is to fasten and grip the strip end at the start of the winding process and thus allow the application of tension. The methodology consists of the development of physical models built close to the real scale, which were submitted to experimental tests with the purpose of identifying the maximum tension of strip winding as a result of the contact arc of the strip with a cylindrical surface similar to the rolling mill mandrel. The model was also used to characterize the friction between the strip and the mandrel. Generally, the winding practice considers that the application of tension can only be started after the wrapping up of at least 1.5 turn of strip onto the mandrel, which generates a decline in physical performance in the rolling mills. The main objective of this work is to evaluate the capacity of the grippers of the mandrel keeping in mind the application of tension with less than a rolling of the strip wound up onto the mandrel. The methodology was applied in three experimental cases in which mandrel segments that are equipped with grippers from three rolling mills were used. The results of the winding tension measured in the physical model in function of the contact arc were shown close to those obtained in the analytical model. A viability analysis for the industrial condition was also carried out, in which the benefits reached with application of the methodology was demonstrated, bearing in mind the high contribution margin of flat steels. The adoption of this methodology will allow the evaluation of the capacity of other grippers projects in order to optimize the strip winding process.